Palmyra, Syria. Developing a Recovery Policy for Sustainable Approaches to Conserving the Heritage and Memory of Damaged Archaeological Sites. Research Carried Out between July and September 2022 - Rumayed, Ousama (e-Forschungsberichte des DAI, 2023)
The destruction of Syria’s war during the long years of armed conflict has deliberately and systematically targeted cultural heritage. Palmyra suffered terrible destruction. Specially the ancient park, where the most important magnificent monuments are located, has been the scene of extreme explosions that destroyed many significant historical monuments and left several others in a situation of partial or complete destruction. Currently, the interested communities of cultural heritage have already started to give proposals for the post-war reconstruction. There is a need to acquire and gather sufficient knowledge about the historical urban development of the archaeological site, building materials, and urban style of each monument in accordance with its identity and authenticity before submitting any proposal for its reconstruction or restoration and preservation (Abdulmawla 2017). Furthermore, there is a need to understand the outstanding universal values of cultural heritage, which also require that the values, qualities, and cultural significance of the property be dearly stated. The management plan of the cultural heritage should focus on the issue of the preservation of those values, in addition to cultural resource management. Thus, the cultural significance of the historical site guides the management policy and consequent strategies for safeguarding and preservation.